A ferromagnetic material and its preparation method and application
By adding non-magnetic elements into the Cr1.5Te2 material to form the MxCr1.5-xTe2 structure, the problem of difficult control in the preparation of existing TMDs two-dimensional ferromagnetics is solved, and the room temperature stable ferromagnetic and high Curie temperature of the material is achieved, which is suitable for high-temperature magnetic storage and spintronics applications.
Patent Information
- Application Number
- CN202410860256.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-06-28
AI Technical Summary
The existing TMDs two-dimensional ferromagnets are difficult to achieve controllable, which hinders the further development of its basic research and practical application.
The MxCr1.5-xTe2 structure is formed by adding non-magnetic elements such as copper, zinc or aluminum into the Cr1.5Te2 ferromagnetic material, and prepared by chemical vapor phase transport method.
It effectively enhances the stable ferromagneticity of the material at room temperature, breaks through the limitations of low-temperature ferromagneticity of traditional two-dimensional materials, and realizes Curie temperature above room temperature, and is suitable for magnetic memory devices and spintronic devices.
Smart Images

Figure CN118888233B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the fields of material science and nanotechnology, and in particular to a ferromagnetic body and a preparation method and application thereof. Background Art
[0002] Since the discovery of graphene, a large number of two-dimensional (2D) materials have been discovered rapidly, including hexagonal boron nitride, two-dimensional transition metal chalcogenides (TMDs) and metal halides. These materials have excellent physical and chemical properties and have potential applications in electronics, optoelectronics, spintronics and catalysis. In recent years, TMDs have attracted great interest due to their gapless electronic structure. They have rich physical properties, including magnetism, charge density waves and superconductivity. In summary, researchers have developed a chemical vapor deposition strategy to synthesize two-dimensional single crystals of different thicknesses. For example, 1T-CrTe2 exhibits magnetic anisotropy and Curie temperature (Tc) affected by layer thickness. This provides a feasible method for studying the unique physical properties of two-dimensional single crystals and fabricating high-temperature electromagnetic devices in the two-dimensional limit.
[0003] Although the Curie temperature of existing TMDs two-dimensional ferromagnets has reached room temperature and some of them have magnetic anisotropy, most TMDs two-dimensional ferromagnets are difficult to prepare in a controllable manner, which seriously hinders their further basic research and potential practical applications. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a ferromagnetic body and a preparation method and application thereof.
[0005] Most of the existing technologies use magnetic elements to obtain or enhance the ferromagnetism of the parent phase, but few studies have used non-magnetic elements to enhance the Tc of TMDs to above room temperature. Compared with magnetic elements, non-magnetic elements can effectively avoid the introduction of other magnetic impurities, and the physical mechanisms of doping magnetic elements and non-magnetic elements in TMDs to enhance ferromagnetism and Tc are completely different in theory. Therefore, it is particularly important to explore the controllable preparation method of TMDs with room temperature Tc and magnetic anisotropy under non-magnetic element doping in practical applications and theoretical exploration.
[0006] In a first aspect, the present invention provides a ferromagnetic body, comprising: x Cr 1.5-x Te2, of which M accounts for M x Cr 1.5-x The percentage of Te2 atoms to the total is A%, and A% satisfies the following relationship:
[0007] A% = x / 3.5 × 100%;
[0008] Among them, the value range of A is 0<A≤5; for example, A is 0.1, 0.5, 1, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.5, 4, 4.5, 5 or any value therebetween.
[0009] In some embodiments, the value range of x is 0<x<1.5; for example, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.3, 0.5, 0.7, 0.9, 1.1, 1.3, 1.4 or any value therebetween.
[0010] In some embodiments, M includes a non-magnetic element. Preferably, M is selected from one or more of copper, zinc, or aluminum.
[0011] Chromium sulfide compounds (Cr m X n , X is S, Se and Te) is a class of ordered layered materials with strong magnetic properties, which has attracted extensive research interest from scholars in recent years. x’ Te y The ferromagnetism of two-dimensional magnetic materials at room temperature is very challenging. Previous research has focused on the ferromagnetism of two-dimensional Cr x’ Te y Magnetic elements are doped into materials to enhance ferromagnetism. However, the introduction of magnetic impurities complicates the physical mechanism, which causes difficulties in theoretical analysis of materials and hinders their practical application. Therefore, the present invention proposes a new method for enhancing the ferromagnetism of two-dimensional magnetic materials by targeted doping with non-magnetic elements, thereby achieving stable ferromagnetism at room temperature.
[0012] In some embodiments, the value range of A is 1≤A≤3.5, preferably 1.5≤A≤3, and more preferably 1.5≤A≤2.5. If the value of A is too large, the Curie temperature (Tc) of the ferromagnetic material will decrease.
[0013] In some embodiments, the value range of x is 0<x<1, preferably 0<x<0.5, and more preferably 0<x<0.2.
[0014] In some embodiments, the ferromagnetic body has a plate-like morphology.
[0015] In some embodiments, the out-of-plane coercive force of the ferromagnet is 30-100 Oe, for example, 35 Oe, 40 Oe, 45 Oe, 50 Oe, 55 Oe, 60 Oe, 65 Oe, 70 Oe, 80 Oe, 90 Oe, 100 Oe or any value therebetween.
[0016] In some embodiments, the in-plane coercive force of the ferromagnet is 5-20 Oe, for example, 7 Oe, 9 Oe, 11 Oe, 13 Oe, 15 Oe, 17 Oe, 19 Oe or any value therebetween.
[0017] In some embodiments, the out-of-plane remanence of the ferromagnet is 0.1-10emu / g, for example, 0.5emu / g, 1emu / g, 1.5emu / g, 2emu / g, 2.5emu / g, 3emu / g, 3.5emu / g, 4emu / g, 4.5emu / g, 5emu / g, 5.5emu / g, 6emu / g, 6.5emu / g, 7emu / g, 7.5emu / g, 8emu / g, 8.5emu / g, 9emu / g, 9.5emu / g or any value therebetween.
[0018] In some embodiments, the in-plane remanence of the ferromagnet is 0.25-25emu / g, for example, 0.5emu / g, 1emu / g, 5emu / g, 10emu / g, 15emu / g, 20emu / g, 25emu / g or any value therebetween.
[0019] In some embodiments, the ferromagnet has a Curie temperature of 310-350K.
[0020] In a second aspect, the present invention provides a method for preparing a ferromagnetic body, comprising the following steps:
[0021] The M source, Te powder, Cr powder and a transport agent are mixed and reacted.
[0022] In some embodiments, the M source is a non-magnetic material.
[0023] In the following embodiments, the M source is selected from one or more of copper, zinc, and aluminum.
[0024] In some embodiments, the molar ratio of the Te powder to the Cr powder is (0.5-2):1; for example, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1 or any value therebetween.
[0025] In some embodiments, the molar ratio of the Te powder to the Cr powder is (0.5-1):1.
[0026] In some embodiments, the molar ratio of Cr powder to M source is 1:(0.01-0.5), for example, 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5 or any value therebetween.
[0027] In some embodiments, the transport agent is selected from iodine.
[0028] In some embodiments, the amount of the transport agent is 25-40% of the mass of the Te powder, for example, 25%, 27%, 29%, 31%, 33%, 35%, 37%, 39% or any value therebetween.
[0029] In some embodiments, the reaction is performed under vacuum conditions.
[0030] In some embodiments, the reaction is performed in a quartz ampoule.
[0031] In some embodiments, the reaction temperature is 800-1000°C; for example, 800°C, 850°C, 900°C, 950°C, 1000°C or any value therebetween.
[0032] In some embodiments, the heating rate of the reaction is 1-5°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min or any value therebetween.
[0033] In some embodiments, the reaction time is 5-10 days, for example, 5 days, 6 days, 7 days, 8 days, 9 days, 10 days or any value therebetween.
[0034] In a third aspect, the present invention provides an application of the ferromagnet described in the first aspect or the ferromagnet obtained by the preparation method described in the second aspect in a magnetic storage device and / or a spintronic device, in particular in a spin-effect transistor device.
[0035] Compared with the prior art, the present invention has the following excellent effects:
[0036] (1) The present invention comprises the following steps: 1.5 Doping non-magnetic materials into Te2 ferromagnetic materials can effectively enhance its stable ferromagnetism at room temperature; it breaks through the limitations of low-temperature ferromagnetism of traditional two-dimensional materials and confirms the effectiveness of doping with non-magnetic elements in achieving room-temperature ferromagnetism. It also provides technical support for its application in magnetic storage devices and spintronic devices.
[0037] (2) The material of the present invention is easy to prepare: the chemical vapor transport method is used, and the preparation process is relatively simple, which improves the material's preparability. The authenticity of the material synthesis is ensured by various characterization methods such as SEM and STEM. The presence of non-magnetic elements in the doped flaky samples was verified, and the ratio of non-magnetic elements to Te and Cr atoms was determined. Using magnetic measurements such as L-TEM and VSM, it was found that the material has a Curie temperature above room temperature and good material stability at room temperature, providing it with broad application prospects in the field of spin electronics. For example, it can be used to prepare devices such as spin field-effect transistors (SFETs) to achieve spin electron transmission at room temperature. Its application in spin electronics is expected to promote the development of the next generation of electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 is the X-ray diffraction pattern of the ferromagnetic crystal material crystal obtained in Example 1;
[0039] Figure 2 (a) is a front scanning electron microscope image of the ferromagnetic crystalline material crystal obtained in Example 1;
[0040] Figure 2 (b) is a side scanning electron microscope image of the ferromagnetic crystalline material crystal obtained in Example 1;
[0041] Figure 3 (a) is a high-angle annular dark-field scanning transmission electron microscope image of the ferromagnetic crystalline material crystal prepared in Example 1;
[0042] Figure 3 (b) is a distribution diagram of the Te element in the ferromagnetic crystal material crystal obtained in Example 1;
[0043] Figure 3 (c) is a distribution diagram of the Cr element in the ferromagnetic crystal material crystal obtained in Example 1;
[0044] Figure 3 (d) is a distribution diagram of the Cu element in the ferromagnetic crystal material crystal obtained in Example 1;
[0045] Figure 4 (a) is a Lorentz electron microscope photograph of the ferromagnetic crystalline material crystal obtained in Example 1 at room temperature;
[0046] Figure 4 (b) is the fringe domain of the ferromagnetic crystal material crystal obtained in Example 1 under zero magnetic field with positive and negative underfocus of 1.8 mm;
[0047] Figure 5 hysteresis loops of IP and OOP of the ferromagnetic crystal material crystal prepared in Example 1;
[0048] Figure 6 This is the MT curve of the ferromagnetic crystalline material prepared in Example 1. DETAILED DESCRIPTION
[0049] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments and drawings. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention.
[0050] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.
[0051] The room temperature in the present invention refers to 20-30°C.
[0052] Example 1
[0053] (1) Preparation of ferromagnetic crystal materials
[0054] Using the chemical vapor transport method (CVT method), elemental Cr (234 mg), Te (638 mg), and Cu (66 mg) powders were mixed in a molar ratio of 1.28:1.42:0.3 and placed in a quartz ampoule tube. A small amount of iodine (200 mg) was used as a transport agent. Then, the quartz ampoule tube was evacuated, the furnace temperature was raised to 950°C at a heating rate of 2°C / min, and kept at a constant temperature of 950°C for 7 days to obtain a ferromagnetic crystalline material.
[0055] (2) Characterization of the prepared ferromagnetic crystal material
[0056] The ferromagnetic crystal material prepared in step (1) was taken out from the quartz ampoule tube, washed with anhydrous ethanol for several times, and the sample was placed in a beaker and dried in a muffle furnace at 50° C. and then sealed for further characterization.
[0057] Figure 1 The red line in the figure is the diffraction peak of the ferromagnetic crystal material prepared in Example 1 of the present invention measured by XRD at room temperature. 1+x The characteristic peaks of Te2 single crystal are Figure 1 The green line shows Figure 1 It can be seen that the ferromagnetic crystal material prepared in this embodiment contains only two diffraction peaks (004) and (008), and the positions of the diffraction peaks are similar to those of Cr.1+x The characteristic peaks of Te2 single crystal are consistent. Figure 1 It can be seen that the ferromagnetic crystal material prepared in this embodiment has high crystal quality, single phase, and is slightly shifted to the right as a whole, which may be caused by Cu doping.
[0058] The surface morphology of the ferromagnetic crystal material was observed using a scanning electron microscope (SEM). Figure 2 As shown in (a), it can be seen that the crystal is in a flake-like shape and has a relatively smooth surface. Figure 2 As shown in (b), it can be seen that the cross section of the sample presents a layered coupling structure with thin layers and dense interlayers.
[0059] The growth direction of the crystal can be analyzed by using the crystal morphology and the corresponding high-resolution image. Therefore, we performed a high-angle annular dark-field scanning transmission electron microscope (STEM) characterization on the crystal prepared in this embodiment to further analyze its crystal structure. The preparation method of the experimental sample adopts the focused ion beam (FIB) milling technology. The experimental sample is observed under SEM to be a lamellar sample, and the sample surface is arranged along the crystal cross section. The obtained STEM characterization results are as follows: Figure 2 As shown, Figure 2 (a) is a front scanning electron microscope image of the crystal obtained in Example 1; Figure 2 (b) is a side scanning electron microscope image of the crystal prepared in Example 1.
[0060] like Figure 3 As shown, elemental analysis of the transferred crystalline nanosheets by energy dispersive spectroscopy (EDS) showed that the nanosheets were composed of Cr, Te, and Cu elements, indicating successful doping. Corresponding EDS elemental mapping image Figure 3 (a)-(d) clearly show the spatial distribution of elements Cu, Cr, and Te. The elements are evenly distributed. Figure 3 (a) Room temperature magnetic domains were observed in the green box. Figure 3 (a) EDS atomic ratio of the selected area shows that the atomic ratio of Te, Cr, and Cu is 2:1.43:0.07, and the atomic ratio of the sum of the atomic ratios of Cu and Cr to Te is 1.5:2; Cu accounts for 2% of the atomic ratio of the ferromagnetic crystal material.
[0061] The magnetic domain structure of the ferromagnetic crystalline material prepared in this embodiment was observed by using a Lorentz transmission electron microscope (L-TEM) at an image tilt angle of 3°, a defocus value of 1.8 mm, and a vertically applied magnetic field at 293 K. Figure 4 shown. Figure 4 (a) is a Lorentz electron microscope photograph of the ferromagnetic crystalline material crystal obtained in Example 1 at room temperature; Figure 4(b) is the stripe domain of the ferromagnetic crystal material prepared in Example 1 with positive and negative underfocus of 1.8 mm under zero magnetic field.
[0062] In L-TEM, the domain wall is formed by the domain wall with an in-plane magnetization component, so the L-TEM image contrast of the narrow bloch-type domain wall is very low and almost invisible. Tilting the sample can expand the projected area of the domain wall on the imaging plane, thereby improving the contrast of the L-TEM image. Such a tilt will make the image contrast more vivid and dark, making the domain wall more obvious. In addition, if it is not tilted, the contrast produced by diffraction caused by scratches and surface oxidation may also mask the magnetic contrast. In the overfocused and underfocused L-TEM images, the contrast of the domain wall is opposite and is invisible under focusing conditions. The existence of magnetic domains indicates that the ferromagnetic crystal material is magnetic at room temperature. In terms of magnetic storage devices, the higher ferromagnetic properties of this ferromagnetic crystal material at room temperature make it an ideal magnetic storage medium.
[0063] The ferromagnetic crystal material was tested for OOP (out-of-plane) and IP (in-plane) hysteresis loops using a vibrating sample magnetometer (VSM). The test results are shown in Figure 2. Figure 5 As shown, the changing trend of the hysteresis loop is consistent with that of ferromagnetic materials. At the same time, it can be seen that IP belongs to the easy magnetization direction relative to OPP. The emergence of this in-plane and out-of-plane difficult and easy axis originates from the asymmetry of the hexagonal crystal structure. This asymmetry makes the magnetocrystalline anisotropy energy in various directions differ greatly.
[0064] Depend on Figure 5 It can be seen that ferromagnetic crystal materials show small coercive force and remanence in both IP and OOP, which enables them to respond faster to changes in external magnetic fields and maintain low remanent magnetization. The coercive force of IP is also lower than that of OOP. The difference between the two is obvious, indicating that the magnetic moment can be reversed under a lower external field in the IP direction. The hysteresis loop of the material shows the characteristics of soft magnetic materials, that is, the hysteresis loop encloses a small area and less energy is lost during magnetization and demagnetization. Figure 6 The MT curve of Example 1 is obtained after the first-order derivative of the MT curve is obtained. When T is 336K, its dM / dT takes the minimum value, so the Curie temperature (Tc) of the ferromagnetic crystalline material prepared in Example 1 is 336K. When the temperature is before Tc, with the increase of temperature, whether it is cold field (FC) or zero cold field (ZFC) mode, M in the IP direction is higher than that in the OOP direction, indicating that its IP direction belongs to the easy magnetization direction. It can be seen that this method not only makes it have magnetic anisotropy, but also obtains Tc at room temperature. The coercive force, remanence and Curie temperature of the ferromagnetic crystalline material are shown in Table 1.
[0065] Example 2
[0066] Preparation of ferromagnetic crystal materials
[0067] Using the chemical vapor transport method (CVT method), elemental Cr (182 mg), Te (638 mg), and Cu (110 mg) powders were mixed in a molar ratio of 1:1.42:0.5 and placed in a quartz ampoule tube. A small amount of iodine (200 mg) was used as a transport agent. Then, the quartz ampoule tube was evacuated, the furnace temperature was raised to 950°C at a heating rate of 2°C / min, and kept in a furnace at 950°C for 7 days to obtain a ferromagnetic crystalline material, wherein Cu accounted for 5% of the atomic ratio of the ferromagnetic crystalline material. The coercive force, remanence, and Curie temperature of the ferromagnetic crystalline material are shown in Table 1.
[0068] Example 3
[0069] Preparation of ferromagnetic crystal materials
[0070] Using the chemical vapor transport method (CVT method), elemental Cr (182 mg), Te (638 mg), and Cu (66 mg) powders were mixed in a molar ratio of 1:1.42:0.3 and placed in a quartz ampoule tube. A small amount of iodine (200 mg) was used as a transport agent. Then, the quartz ampoule tube was evacuated, the furnace temperature was raised to 950°C at a heating rate of 2°C / min, and kept in a furnace at 950°C for 7 days to obtain a ferromagnetic crystalline material, in which Cu accounted for 4% of the atomic ratio of the ferromagnetic crystalline material. After testing, the Curie temperature of the ferromagnetic crystalline material was 329K.
[0071] Comparative Example 1
[0072] Preparation of Cr 1.5 Te2
[0073] Using the chemical vapor transport method (CVT method), Cr (234 mg), Te (638 mg), and Cu (0 mg) powders were mixed in a molar ratio of 1.28:1.42:0 and placed in a quartz ampoule tube. A small amount of iodine (200 mg) was used as a transport agent. Then, the quartz ampoule tube was evacuated, the furnace temperature was raised to 950°C at a heating rate of 2°C / min, and kept in a furnace at 950°C for 7 days. After testing, Cr 1.5 The Curie temperature of Te2 is 303K.
[0074] Table 1
[0075]
[0076] According to the above examples and comparative examples, it can be seen that when comparative example 1 is not doped with copper, Tc is 303K, and when the copper content is increased to 2% (example 1), Tc is 336K; but when the copper content is higher than 2% (such as examples 2 and 3), Tc decreases with the increase of copper content. Therefore, the increase of Tc is not proportional to the increase of copper content.
[0077] Therefore, the ferromagnetic crystalline material (i.e., M x Cr 1.5-x Te2 crystal) has high ferromagnetic properties at room temperature and can be used as an ideal magnetic storage medium. x Cr 1.5-x Te2 crystal) has a higher Curie temperature than the comparative example.
[0078] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A ferromagnetic material comprising: x Cr 1.5-x Te2, M accounts for M x Cr 1.5-x The percentage of Te2 atoms to the total is A%, and A% satisfies the following relationship: A% = x / 3.5 × 100%; in, The value range of A is 1.5≤A≤3; and / or The value range of x is 0<x<0.1; M includes a non-magnetic element, and M is selected from one or more of copper, zinc, or aluminum.
2. The ferromagnetic body according to claim 1, characterized in that The value range of A is 1.5≤A≤2.
5.
3. The ferromagnetic body according to claim 1, characterized in that: The ferromagnetic body has a flake-like morphology.
4. The ferromagnetic body according to any one of claims 1 to 3, characterized in that: The out-of-plane coercive force of the ferromagnetic material is 30-100 Oe, and / or The in-plane coercive force of the ferromagnetic body is 5-20 Oe, and / or The out-of-plane remanence of the ferromagnetic material is 0.1-10emu / g, and / or The in-plane remanence of the ferromagnetic material is 0.25-25emu / g, and / or The Curie temperature of the ferromagnet is 310-350K.
5. A method for preparing a ferromagnetic body, comprising the following steps: Mixing the M source, Te powder, Cr powder and a transport agent and reacting them; The M source is a non-magnetic material, and the M source is selected from one or more of copper, zinc, and aluminum; The molar ratio of the Te powder to the Cr powder is (0.5-1.2):1; the molar ratio of the Cr powder to the M source is 1:(0.01-0.25).
6. The preparation method according to claim 5, characterized in that: The transport agent is selected from iodine; The amount of the transport agent used is 25-40% of the mass of the Te powder.
7. The preparation method according to claim 5, characterized in that: The reaction is carried out under vacuum conditions; and / or The reaction was carried out in quartz ampoule tubes.
8. The preparation method according to claim 5, characterized in that: The reaction temperature is 800-1000°C; and / or The heating rate of the reaction is 1-5°C / min; and / or The reaction time is 5-10 days.
9. Use of the ferromagnetic material according to any one of claims 1 to 4 or the ferromagnetic material obtained by the preparation method according to any one of claims 5 to 8 in a magnetic storage device and / or a spintronic device.
10. Use of the ferromagnetic material according to any one of claims 1 to 4 or the ferromagnetic material obtained by the preparation method according to any one of claims 5 to 8 in a selective effect transistor device.